1988
DOI: 10.1126/science.2964084
|View full text |Cite
|
Sign up to set email alerts
|

The Fos Complex and Fos-Related Antigens Recognize Sequence Elements That Co ntain AP-1 Binding Sites

Abstract: The Fos protein complex and several Fos-related antigens bind directly or indirectly to a common sequence element that is similar to the consensus binding site for HeLa cell activator protein 1 (AP-1). This element is present in a negative regulatory sequence in the differentiation-sensitive adipocyte gene, aP2; in a transcriptional enhancer for the Gibbon ape leukemia virus; and in a region of the human immunodeficiency virus (HIV) long terminal repeat partially characterized as a negative regulatory element.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
244
1
7

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(258 citation statements)
references
References 29 publications
6
244
1
7
Order By: Relevance
“…The potential transcriptional regulation of HIV-1 gene expression by the AP-1 binding site within NRE is further supported by the fact that Curran and his colleagues have identified two additional AP-1 sites in this LTR region (8). However, the novel AP-1 site we found within the TAR region appears to be of even greater interest.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…The potential transcriptional regulation of HIV-1 gene expression by the AP-1 binding site within NRE is further supported by the fact that Curran and his colleagues have identified two additional AP-1 sites in this LTR region (8). However, the novel AP-1 site we found within the TAR region appears to be of even greater interest.…”
Section: Resultssupporting
confidence: 55%
“…Sequences between nucleotides -348 to -343 and -336 to -331 are similar to HeLa cell AP-1 binding sites and have been shown to interact with the FOS-complex and FOS-related antigens (8). In this study we have further examined the HIV-1 LTR, and we have identified three additional AP-1 binding sites one of which was found within the TAR element.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…For example, in the lysis/lysogeny switch of bacteriophage λ, cro and repressor compete for related sites in the rightward operator 28 . In eukaryotes, a number of regulatory proteins have been shown to be members of protein families with related DNA-binding specificities [29][30][31][32][33][34][35][36][37] . In fact, a member of the nuclear hormone receptor family, thyroid hormone receptor, was recently shown to mediate negative effects on transcription from oestrogen-responsive DNA elements, apparently by competing with oestrogen receptor for binding to the elements 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The Fos, Jun, and JunB proteins have been shown to form activator protein 1 (AP-1) through a conserved dimerization domain, i.e., the leucine zipper [13]. Transcription regulator AP-1 protein binds a specific DNA motif and is believed to transactivate the expression of a number of late effector genes [14][15][16][17][18][19]. In the ischemic brain, we have previously demonstrated an increase in AP-1 binding activity [9].…”
mentioning
confidence: 99%